Advantages of Copyright Law in the Digital Age: Challenges and Opportunities for Content Creators (Journal of Intellectual Property Rights (JIPR), 2025)
The research aims to observe the benefits of copyright law in the digital age by understanding the challenges faced and identifyingopportunities for content creators. Copyright in the digital age presents unique challenges and opportunities; challenges mainly centered on law enforcement and copyright infringements and opportunities connected with accessibility and creative development opportunities provided by digital technologies. The research method used is a qualitative approach through literature research. The data used are secondary data. The research sources include academic articles, laws, and regulations related to copyright, as well as other quality literature. This research finds that copyright law in the digital age has complex and challenging dynamics. Copyright violations often occur because of the ease of sharing and copying content online, making law enforcement often difficult. Nevertheless, the digital age also provides opportunities for content creators, such as ease in reaching global audiences and opportunities for creative innovation. Therefore, content creators must have sufficient knowledge of copyright to be able to protect and maximize the value of their work in the digital age. The findings of this research underscore the importance of copyright knowledge for content creators in the digital age.